Thermoplastic polyester resin composition
By reasonably formulating a variety of resins and filler components in the polyester resin composition, the problems of severe shrinkage marks and insufficient toughness when the ribs or protrusions are arranged are solved, and a polyester resin composition with high toughness, heat resistance and excellent appearance are achieved.
Patent Information
- Application Number
- CN202080018211.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-06
- Filing Date
- 2020-02-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-02-28
AI Technical Summary
When the conventional polyester resin composition is provided with ribs or protrusions on the molded article, shrinkage marks are prone to occur, which affects the appearance, and is insufficient in toughness, making it difficult to meet practical strength requirements.
By reasonably preparing the polybutylene terephthalate resin, polyethylene terephthalate resin, thermoplastic polyester elastomer, epoxy group-containing ethylene copolymer, spherical and/or amorphous inorganic filler, glass fiber reinforcement, polycarbonate resin and transesterification inhibitor in the polyester resin composition, the ratio of each component is adjusted to form a polyester resin composition that has improved shrinkage, imparts high toughness and excellent heat resistance.
It realizes that while maintaining high toughness and excellent heat resistance, it significantly improves the shrink mark problem of molded products, ensuring that the appearance and mechanical properties of molded products reach an excellent level.
Smart Images

Figure CN113508160B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic polyester resin composition capable of suppressing the generation of sink marks and obtaining a molded product with high toughness. Background Art
[0002] Generally, polyester resins have excellent mechanical properties, heat resistance, chemical resistance, etc., and are widely used in automobile parts, electrical and / or electronic parts, household sundries, etc. From the perspective of weight reduction and cost reduction, thin-walled products are being developed. In order to meet practical strength even with a thin thickness, the following settings are made: a resin composition reinforced with glass fiber is used, and a large number of ribs or protrusions are configured to strengthen the molded body.
[0003] However, if ribs or protrusions are provided on a molded product, sink marks become noticeable and may impair the appearance.
[0004] In order to improve the above-mentioned problems, a method is proposed in patent documents 1 and 2, which suppresses crystallinity by adding amorphous polyamide or difficult-crystallization polyamide to crystalline polyamide and glass fiber, and improves shrinkage by adding spherical fillers to suppress shrinkage in the thickness direction, but when adding amorphous components and spherical fillers, there are problems of reduced flexure and insufficient toughness. In addition, a method is proposed in patent document 3, in the combination of crystalline polyamide and amorphous or difficult-crystallization polyamide, adding special-section glass and olefin resin, adding spherical and / or amorphous inorganic fillers, and further adding olefin elastomers to give toughness, but there is no mention of shrinkage. In addition, in patent document 4, a polyester resin composition is proposed, which is in the combination of polybutylene terephthalate resin and aromatic polycarbonate resin or polyethylene terephthalate resin, mixed with impact-resistant modifiers such as elastomers, inorganic fillers, aromatic polycarboxylates, and epoxy compounds, but there is no mention of shrinkage, and there are problems such as aromatic polycarboxylates seeping out on the surface of molded products.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2009-7482
[0008] Patent Document 2: Japanese Patent Application Publication No. 2013-203869
[0009] Patent Document 3: Japanese Patent No. 5407530
[0010] Patent Document 4: Japanese Patent No. 3933838 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] An object of the present invention is to provide a polyester resin composition which improves the sink mark of a molded article, imparts toughness, and has excellent heat resistance.
[0013] Means for solving technical problems
[0014] In order to solve the above-mentioned technical problems, the inventors of the present invention conducted an in-depth discussion on the composition and characteristics of the polyester resin composition. As a result, it was found that the above-mentioned technical problems can be achieved by containing an appropriate amount of a specific resin and appropriately adjusting the ratio of each component, thereby completing the present invention.
[0015] That is, the present invention has the following configurations.
[0016] [1] A polyester resin composition comprising 18 to 35 parts by mass of a polybutylene terephthalate resin (A), 10 to 25 parts by mass of a polyethylene terephthalate resin (B), 10 to 20 parts by mass of a thermoplastic polyester elastomer (C), 0.5 to 5 parts by mass of an epoxy group-containing ethylene copolymer (D), 12 to 20 parts by mass of a spherical and / or amorphous inorganic filler (E), 10 to 35 parts by mass of a glass fiber reinforcement (F), 0 to 10 parts by mass of a polycarbonate resin (G), and 0 to 2 parts by mass of an ester exchange inhibitor (H).
[0017] [2] The polyester resin composition according to [1], further comprising 4 to 8 parts by mass of a copolymerized polyethylene terephthalate resin (I) and / or a copolymerized polybutylene terephthalate resin (J).
[0018] [3] A polyester resin composition as described in [1] or [2], characterized in that the depth of the sink mark on the back of the rib of a molded product (45 mm×100 mm×2 mm thick (having a rib of 14 mm long, 2 mm high, and 1 mm thick, and a 100 mm side having a 6 mm wall)) obtained by injection molding the polyester resin composition at a barrel temperature of 270°C and a mold temperature of 80°C is less than 3.0 μm.
[0019] Effects of the Invention
[0020] According to the present invention, a polyester resin composition can be provided which improves the sink mark of a molded article, imparts high toughness, and has excellent heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram showing a molded product used for evaluation of sink marks in Examples of the present invention viewed from three directions. DETAILED DESCRIPTION
[0022] Hereinafter, the present invention will be described in detail.
[0023] Unless otherwise specified, the content (mixture) of each component constituting the polyester resin composition is the amount (parts by mass) when the mass of the polyester resin composition is 100 parts by mass. The mixing amount (mixing ratio) of each component is the content (content ratio) in the polyester resin composition.
[0024] The polybutylene terephthalate resin (A) in the present invention is the main resin component of all polyester resins in the resin composition of the present invention. It is preferred that the content is the highest among all polyester resins. There is no particular limitation on the polybutylene terephthalate resin (A), and it is preferred to use a homopolymer composed of terephthalic acid and 1,4-butanediol. In addition, within the range of not damaging the moldability, crystallinity, surface gloss, etc., when all the acid components constituting the polybutylene terephthalate resin (A) are set to 100 mol% and all the diol components are set to 100 mol%, other components can be copolymerized up to about 5 mol%. As other components, the components used in the copolymerized polybutylene terephthalate resin (J) described below can be listed.
[0025] As a measure of the molecular weight of the polybutylene terephthalate resin (A), the reduced viscosity (0.1 g of the sample is dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30°C using an Ubbelohde viscometer) is preferably in the range of 0.6 to 0.9 dl / g, and more preferably in the range of 0.7 to 0.8 dl / g. When the reduced viscosity is less than 0.6 dl / g, the toughness of the resin is greatly reduced, and the fluidity is too high, resulting in burrs being easily generated. On the other hand, if it exceeds 0.9 dl / g, the fluidity of the present composition system may be reduced.
[0026] The content of the polybutylene terephthalate resin (A) is 18 to 35 parts by mass, preferably 20 to 33 parts by mass. By containing (mixing) the polybutylene terephthalate resin (A) within this range, various properties can be satisfied.
[0027] The polyethylene terephthalate resin (B) in the present invention is basically a homopolymer of ethylene terephthalate units. In addition, when all acid components constituting the polyethylene terephthalate resin (B) are 100 mol% and all diol components are 100 mol%, other components can be copolymerized up to about 5 mol% within the range that does not impair various properties. As other components, the components used in the copolymerized polyethylene terephthalate resin (I) described below can be cited. As other components, diethylene glycol generated by condensation of ethylene glycol during superposition is included.
[0028] As a measure of the molecular weight of the polyethylene terephthalate resin (B), the reduced viscosity (0.1 g of a sample is dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30° C. using an Ubbelohde viscometer) is preferably in the range of 0.4 to 1.0 dl / g, and more preferably in the range of 0.5 to 0.9 dl / g. If the reduced viscosity is less than 0.4 dl / g, the strength of the resin may be reduced, and if it exceeds 1.0 dl / g, the fluidity of the resin may be reduced.
[0029] The content of the polyethylene terephthalate resin (B) is 10 to 25 parts by mass, preferably 13 to 22 parts by mass. By containing (mixing) the polyethylene terephthalate resin (B) within this range, various properties can be satisfied.
[0030] The thermoplastic polyester elastomer (C) in the present invention preferably has the following hard segment and the following soft segment as main components (70% by mass or more): the above-mentioned hard segment is composed of a crystalline polyester composed of an aromatic dicarboxylic acid and an aliphatic or alicyclic diol, and the above-mentioned soft segment is at least one selected from aliphatic polyethers, aliphatic polyesters and aliphatic polycarbonates.
[0031] In the thermoplastic polyester elastomer (C), the aromatic dicarboxylic acid constituting the hard segment polyester is preferably terephthalic acid or naphthalene dicarboxylic acid. Other acid components include aromatic dicarboxylic acids such as diphthalic acid, isophthalic acid, and sodium 5-sulfoisophthalic acid; alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid and tetrahydrophthalic anhydride; and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, and hydrogenated dimer acid. These are used within a range that does not significantly reduce the melting point of the resin, and the amount thereof is less than 30 mol %, preferably less than 20 mol %, of the total acid components.
[0032] In the thermoplastic polyester elastomer (C), the aliphatic or alicyclic diol constituting the hard segment polyester is widely used in general aliphatic or alicyclic diols, and is not particularly limited, but is preferably mainly an alkylene glycol having 2 to 8 carbon atoms. Specifically, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, etc. are listed. 1,4-butanediol and 1,4-cyclohexanedimethanol are most preferred.
[0033] As the polyester component constituting the hard segment, a component containing a butylene terephthalate unit or a butylene naphthalate unit is preferred from the viewpoint of physical properties, moldability, and cost performance.
[0034] In the thermoplastic polyester elastomer (C), an aromatic polyester suitable for constituting the polyester of the hard segment can be easily obtained by a common polyester production method. In addition, the polyester preferably has a number average molecular weight of 10,000 to 40,000.
[0035] In the thermoplastic polyester elastomer (C), examples of aliphatic polyethers as soft segment components include poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, copolymers of ethylene oxide and propylene oxide, ethylene oxide addition polymers of poly(propylene oxide) glycol, copolymers of ethylene oxide and tetrahydrofuran, and the like.
[0036] Among the above-mentioned aliphatic polyethers, poly(tetramethylene oxide) glycol, ethylene oxide adducts of poly(propylene oxide) glycol, and copolymers of ethylene oxide and tetrahydrofuran are preferred, and poly(tetramethylene oxide) glycol and ethylene oxide adducts of poly(propylene oxide) glycol are more preferred. In addition, the number average molecular weight of these soft segments is preferably about 300 to 6000 in the copolymerized state.
[0037] The copolymerization amount of the soft segment of the thermoplastic polyester elastomer (C) is preferably 10 to 85% by mass, more preferably 20 to 85% by mass.
[0038] Thermoplastic polyester elastomer (C) can be produced by a currently known method. For example, the following methods can be used: a method in which a lower alcohol diester of a dicarboxylic acid, an excess of a low molecular weight diol and a soft segment component are subjected to ester exchange in the presence of a catalyst, and the obtained reaction product is subjected to polycondensation; a method in which a dicarboxylic acid, an excess of a diol and a soft segment component are subjected to an esterification reaction in the presence of a catalyst, and the obtained reaction product is subjected to polycondensation. The content of component (C) is 10 to 20 parts by mass, preferably 10 to 18 parts by mass, more preferably 10 to 17 parts by mass, and further preferably 11 to 15 parts by mass. When it is less than 10 parts by mass, the total energy absorption (curve SS area) during the bending test cannot be obtained sufficiently, and the toughness is insufficient, so it is not preferred. Even if more than 20 parts by mass are added, the effect of the addition cannot be obtained and the heat resistance is reduced.
[0039] The epoxy-containing ethylene copolymer (D) of the present invention is preferably an epoxy-containing ethylene copolymer comprising 50 to 99% by mass of ethylene units, 0.1 to 30% by mass (preferably 0.5 to 20% by mass) of unsaturated carboxylic acid glycidyl ester units or unsaturated glycidyl ether units, and 0 to 49% by mass of ethylenically unsaturated ester compound units.
[0040] In the epoxy-containing ethylene copolymer (D), examples of the unsaturated carboxylic acid glycidyl ester unit and the unsaturated glycidyl ether unit include glycidyl acrylate, glycidyl methacrylate, glycidyl itaconate, glycidyl acrylate, allyl glycidyl ether, 2-methylallyl glycidyl ether, and styrene-p-glycidyl ether.
[0041] In addition, in the epoxy-containing ethylene copolymer (D), a copolymer of unsaturated carboxylic acid glycidyl ester or unsaturated glycidyl ether with ethylene and ethylene-based unsaturated ester compounds having a valence of 3 or more can also be used. Examples of the ethylene-based unsaturated ester compound include vinyl carboxylate such as vinyl acetate, vinyl propionate, methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and α,β-unsaturated carboxylic acid alkyl esters. Vinyl acetate, methyl acrylate, and ethyl acrylate are particularly preferred.
[0042] Examples of the epoxy-containing ethylene copolymer (D) include copolymers composed of ethylene units and glycidyl methacrylate units, copolymers composed of ethylene units, glycidyl methacrylate units and methyl acrylate units, copolymers composed of ethylene units, glycidyl methacrylate units and ethyl acrylate units, and copolymers composed of ethylene units, glycidyl methacrylate units and vinyl acetate units.
[0043] The content of the epoxy-containing ethylene copolymer (D) is 0.5 to 5 parts by mass, preferably 1 to 4 parts by mass. When it is less than 0.5 parts by mass, it is not preferred because the total energy absorption (curve SS area) during the bending test cannot be obtained sufficiently, and the toughness is insufficient. When more than 5 parts by mass are added, a good appearance cannot be obtained, so it is not preferred. In addition, by combining the thermoplastic polyester elastomer (C) and the epoxy-containing ethylene copolymer (D), the effect of improving toughness can be further enhanced, so that a polyester composition with sufficient toughness can be obtained while suppressing the reduction in toughness caused by the presence of spherical and / or amorphous inorganic fillers (E), improving sink marks, and having sufficient toughness.
[0044] The spherical or amorphous inorganic filler (E) in the present invention means that the inorganic filler has a spherical and / or amorphous shape rather than a fibrous or plate-like inorganic filler. The spherical and / or amorphous shape means that the major and minor diameters (major diameter / minor diameter), flatness (minor diameter / thickness), and aspect ratio (projected area diameter / thickness) are all 3.0 or less, preferably 2.0 or less. When these values exceed 3.0, the weld strength tends to decrease.
[0045] Specifically, glass beads, silicon dioxide, calcium carbonate, wollastonite, barium sulfate, needle-shaped small pieces of wollastonite and granular aluminum borate can be listed, but it is not limited to these. In addition, even materials treated with commonly known coupling agents can be used without any problem. The particle size of the spherical and / or amorphous inorganic filler (E) is not particularly limited, and any material can be used. For example, the particle size is preferably 1 to 80 μm, and the particle size is more preferably 2 to 30 μm.
[0046] The content of the spherical or amorphous inorganic filler (E) is 12 to 20 parts by mass, preferably 13 to 18 parts by mass. By containing (mixing) the spherical or amorphous inorganic filler (E) within this range, various properties can be satisfied, especially improvement of sink marks.
[0047] The glass fiber reinforcement (F) in the present invention preferably uses milled fibers as glass short fibers with an average fiber diameter of about 4 to 20 μm and a cut length of about 30 to 150 μm; and fibers in the form of chopped strands with an average fiber diameter of about 1 to 20 μm and a cut fiber length of about 1 to 20 mm. As the cross-sectional shape of the glass fiber, glass fibers with circular cross-sections and non-circular cross-sections can be used. As glass fibers with circular cross-sectional shapes, very general fibers with an average fiber diameter of about 4 to 20 μm and a cut length of about 2 to 6 mm can be used. Glass fibers with non-circular cross-sections include fibers that are approximately elliptical, approximately oblong, and approximately cocoon-shaped in a cross section perpendicular to the length direction of the fiber, and preferably have a flatness of 1.3 to 8. Here, flatness refers to the ratio of the major diameter / minor diameter when the length of the long side of the rectangle with the minimum area circumscribed by the cross section perpendicular to the length direction of the glass fiber is assumed to be the major diameter and the length of the short side is the minor diameter. The thickness of the glass fiber is not particularly limited, but fibers having a short diameter of about 1 to 20 μm and a long diameter of about 2 to 100 μm can be used. These fibers may be used alone or in combination of two or more.
[0048] The average fiber diameter and average fiber length of the glass fibers can be measured by electron microscope observation.
[0049] As these glass fibers, fibers pretreated with a conventionally known coupling agent such as an organic silane compound, an organic titanium compound, an organic borane compound, or an epoxy compound can be preferably used.
[0050] The content of the glass fiber reinforcement (F) is 10 to 35 parts by mass, preferably 13 to 32 parts by mass. By containing (mixing) the glass fiber reinforcement (F) within this range, various properties can be satisfied.
[0051] The polycarbonate in the polycarbonate resin (G) of the present invention can be manufactured by a solvent method, that is, in a solvent such as dichloromethane, in the presence of a known acid acceptor and a molecular weight modifier, by a reaction of a dihydric phenol with a carbonate precursor such as phosgene or an ester exchange reaction of a dihydric phenol with a carbonate precursor such as diphenyl carbonate. Here, as the dihydric phenol preferably used, there are bisphenols, especially 2,2-bis(4-hydroxyphenyl)propane, i.e. bisphenol A. In addition, part or all of bisphenol A can be replaced by other dihydric phenols. As dihydric phenols other than bisphenol A, compounds such as hydroquinone, 4,4-dihydroxydiphenyl, and bis(4-hydroxyphenyl)alkane, or halogenated bisphenols such as bis(3,5-dibromo-4-hydroxyphenyl)propane and bis(3,5-dichloro-4-hydroxyphenyl)propane can be cited. The polycarbonate can be a homopolymer using one dihydric phenol or a copolymer using two or more. The polycarbonate resin (G) is preferably a resin composed only of polycarbonate. The polycarbonate resin (G) may be a resin copolymerized with a component other than polycarbonate (eg, a polyester component) within a range (20% by mass or less) that does not impair the effects of the present invention.
[0052] The polycarbonate resin (G) used in the present invention preferably has high fluidity, and the melt volume flow rate (unit: cm 3 The melt volume flow rate is preferably 20 to 100, more preferably 25 to 95, and even more preferably 30 to 90. When a resin with a melt volume flow rate of less than 20 is used, the fluidity is greatly reduced, the strand stability is reduced, and the moldability is deteriorated. When the melt volume flow rate exceeds 100, the physical properties are reduced due to the low molecular weight, and problems such as gas generation due to decomposition are likely to occur.
[0053] The content of the polycarbonate resin (G) used in the present invention is 0 to 10 parts by mass. The polycarbonate resin (G) may not be contained, but by containing the polycarbonate resin (G), the sink mark is further reduced. When the polycarbonate resin (G) is contained, it is preferably 5 to 9 parts by mass. When it exceeds 10 parts by mass, it is easy to cause deterioration of molding cycle due to reduced crystallinity, poor appearance due to reduced fluidity, etc., so it is not preferred.
[0054] The ester exchange inhibitor (H) in the present invention, as its name suggests, refers to a stabilizer that prevents the ester exchange reaction of polyester resins. In alloys between polyester resins, no matter how the conditions during manufacturing are optimized, a lot of ester exchange reactions will occur due to the application of thermal processes. If the degree of reaction is very large, the expected properties cannot be obtained through the alloy. In particular, ester exchange between polybutylene terephthalate resin and polycarbonate resin often occurs, so the crystallinity of polybutylene terephthalate is greatly reduced at this time, so it is not preferred. In the present invention, by adding component (H), the ester exchange reaction between polybutylene terephthalate resin (A) and polycarbonate resin (G) can be prevented, thereby maintaining appropriate crystallinity.
[0055] As the transesterification inhibitor (H), a phosphorus compound having a catalytic deactivation effect on the polyester resin can be preferably used, and for example, "ADEKA STAB AX-71" manufactured by ADEKA Corporation can be used.
[0056] The content of the transesterification inhibitor (H) used in the present invention is 0 to 2 parts by mass. When the polycarbonate resin (G) is contained, the content of the transesterification inhibitor (H) is preferably 0.05 to 2 parts by mass. When the content of the transesterification inhibitor (H) is less than 0.05 parts by mass, the desired transesterification prevention performance is often not achieved. On the contrary, even if more than 2 parts by mass is added, the effect is hardly noticeable, and sometimes it becomes a factor that increases gas, etc.
[0057] In the present invention, the copolymerized polyethylene terephthalate resin (I) and / or the polybutylene terephthalate resin (J) are preferably mixed in order to suppress poor appearance due to bubbling of glass fibers and poor mold transfer.
[0058] The copolymerized polyethylene terephthalate resin (I) in the present invention refers to when all acid components constituting the copolymer are set to 100 mol% and all glycol components constituting the copolymer are set to 100 mol%. Ethylene glycol is 40 mol% or more and the total of terephthalic acid and ethylene glycol accounts for 80 to 180 mol%. As a copolymer component, it can contain at least one selected from isophthalic acid, sebacic acid, adipic acid, trimellitic acid, 2,6-naphthalene dicarboxylic acid, diethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,4-butanediol, 1,2-propylene glycol, 1,3-propylene glycol and 2-methyl-1,3-propylene glycol as a copolymer component, and preferably amorphous. Among them, as a copolymer component, neopentyl glycol or a combination of neopentyl glycol and isophthalic acid is preferred from the viewpoint of various properties. As a copolymer component, 1,4-butanediol is preferably 20 mol% or less.
[0059] When all diol components constituting the copolymerized polyethylene terephthalate resin (I) are taken as 100 mol %, the copolymerization ratio of neopentyl glycol is preferably 20 to 60 mol %, more preferably 25 to 50 mol %.
[0060] When all the acid components constituting the copolymerized polyethylene terephthalate resin (I) are taken as 100 mol %, the copolymerization ratio of isophthalic acid is preferably 20 to 60 mol %, more preferably 25 to 50 mol %.
[0061] The molecular weight of the copolymerized polyethylene terephthalate resin (I) varies slightly depending on the specific copolymer components, but the reduced viscosity (0.1 g of a sample is dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured using an Ubbelohde viscometer at 30° C.) is preferably 0.4 to 1.5 dl / g, more preferably 0.4 to 1.3 dl / g. If it is less than 0.4 dl / g, the toughness may be reduced, and if it exceeds 1.5 dl / g, the fluidity may be reduced.
[0062] The copolymerized polybutylene terephthalate resin (J) in the present invention is a resin in which 1,4-butanediol accounts for 80 mol% or more and the total amount of terephthalic acid and 1,4-butanediol accounts for 120 to 180 mol% when all the acid components and all the diol components are 100 mol%. The copolymerized polybutylene terephthalate resin (J) may contain at least one selected from isophthalic acid, sebacic acid, adipic acid, trimellitic acid, 2,6-naphthalene dicarboxylic acid, ethylene glycol, diethylene glycol, neopentyl glycol, 1,4-cyclohexanedimethanol, 1,4-butanediol, 1,2-propylene glycol, 1,3-propylene glycol and 2-methyl-1,3-propanediol as the copolymerized component. Among them, isophthalic acid is preferred as the copolymer component, and when all acid components constituting the copolymerized polybutylene terephthalate resin (J) are set to 100 mol%, the copolymerization ratio is preferably 20 to 80 mol%, and more preferably 20 to 60 mol%. When the copolymerization ratio is less than 20 mol%, the transferability to the mold is poor, and there is a tendency that it is difficult to obtain a sufficient appearance. When the copolymerization amount exceeds 80 mol%, there is a possibility that the molding cycle is reduced and the demolding property is reduced.
[0063] The molecular weight of the copolymerized polybutylene terephthalate resin (J) varies slightly depending on the specific copolymer components, but the reduced viscosity (0.1 g of a sample is dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured using an Ubbelohde viscometer at 30° C.) is preferably 0.4 to 1.5 dl / g, more preferably 0.4 to 1.3 dl / g. If it is less than 0.4 dl / g, the toughness may be reduced, and if it exceeds 1.5 dl / g, the fluidity may be reduced.
[0064] The content of the copolymerized polyethylene terephthalate resin (I) and / or the polybutylene terephthalate resin (J) is preferably 4 to 8 parts by weight. When both the copolymerized polyethylene terephthalate resin (I) and the polybutylene terephthalate resin (J) are contained, the total content is used. When the content is less than 4 parts by weight, the effect of suppressing the poor appearance caused by the bubbling of glass fibers and poor mold transfer is almost impossible. When the content exceeds 8 parts by weight, although the appearance of the molded product is good, the molding cycle becomes longer.
[0065] In addition, the polyester resin composition of the present invention may contain various known additives as required within the range that does not impair the characteristics of the present invention. Examples of known additives include colorants such as pigments, mold release agents, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, denaturants, antistatic agents, flame retardants, dyes, and the like. When the polyester resin composition is 100 parts by mass, these various additives may be contained up to 5 parts by mass. That is, in 100 parts by mass of the polyester resin composition, the sum of the above (A), (B), (C), (D), (E), (F), (G), (H), (I), and (J) is preferably 95 to 100 parts by mass.
[0066] As the release agent, long-chain fatty acids or their esters, metal salts, amide compounds, polyethylene wax, silicon, polyethylene oxide, etc. can be cited. As long-chain fatty acids, those with more than 12 carbon atoms are particularly preferred, such as stearic acid, 12-hydroxystearic acid, behenic acid, montanic acid, etc., and part or all of the carboxylic acids can be esterified by monoglycol or polyglycol, or can form metal salts. As amide compounds, ethylene bis terephthalamide, methylene bis stearamide, etc. can be cited. These release agents can be used alone or as a mixture.
[0067] As a method for manufacturing the polyester resin composition of the present invention, the above-mentioned components and various stabilizers, pigments, etc. as required can be mixed and manufactured by melt kneading. The melt kneading method can use any method known to those skilled in the art, and can use a single-screw extruder, a twin-screw extruder, a pressure kneading machine, a Banbury mixer, etc. Among them, a twin-screw extruder is preferably used. As a general melt kneading condition, in a twin-screw extruder, the barrel temperature is 240 to 280° C., and the kneading time is 2 to 15 minutes.
[0068] The sink mark depth on the back of the rib of a molded product (45 mm×100 mm×2 mm thick (having a rib of 14 mm long, 2 mm high, 1 mm thick, and a wall of 6 mm on a 100 mm side)) obtained by injection molding the polyester resin composition of the present invention at a barrel temperature of 270°C and a mold temperature of 80°C can be set to 3.0 μm or less. Figure 1 described.
[0069] Example
[0070] The present invention is further described in detail below by way of examples, but the present invention is not limited to these examples. In addition, the measured values recorded in the examples are obtained by measuring the following method using an injection molding machine (product name: "EC100N", manufactured by Toshiba Machine Co., Ltd.) at a barrel temperature of 270°C and a mold temperature of 80°C to obtain a molded product.
[0071] (1) Flexural strength, flexural modulus, flexural deflection, SS area of the curve
[0072] The measurement was performed in accordance with ISO-178, and the curve SS area was calculated from the total bending strength per bending deflection of 0.0196%.
[0073] (2) Heat deformation temperature
[0074] A multipurpose test piece of ISO-3167 was molded. The heat deformation temperature of the multipurpose test piece under a high load (1.80 MPa) was measured in accordance with ISO-75.
[0075] (3) Appearance of molded products
[0076] When the polyester resin composition is injection molded at a cylinder temperature of 270°C and a mold temperature of 80°C to form a molded product of 100 mm×100 mm×2 mm, the appearance of the molded product obtained by molding at an extrusion speed with a filling time of 1 second is visually observed. If it is "◎", "○", or "△", it is a passing level.
[0077] ◎: Glossy surface, no appearance defects, good
[0078] ○: Almost no appearance defects due to the floating of glass fibers, inorganic fillers, etc. were found on the surface; Good
[0079] △: Some appearance defects occur in some areas (especially at the ends of the molded product and near the gate).
[0080] ×: The entire molded body has a defective appearance
[0081] (4) Sink mark evaluation
[0082] The polyester resin composition was injection molded at a barrel temperature of 270°C and a mold temperature of 80°C to obtain a molded product (45 mm×100 mm×2 mm thick (having a rib of 14 mm in length, 2 mm in height, and 1 mm in thickness, and a 100 mm side having a wall of 6 mm)). A laser microscope (trade name: "Color 3D Laser Microscope VK-9700, manufactured by KEYENCE Co., Ltd.) was used to observe the portion of the molded product with ribs from the back of the molded product at a magnification of 10 times, and the surface height difference (depth of the sink mark) between the rib and the portion without ribs was measured. If the surface height difference is less than 2.5 μm, it is "◎", if it is more than 2.5 and less than 3.0 μm, it is "○", and if it exceeds 3.0 μm, it is unqualified "×". The shape of the molded body is as follows Figure 1 shown.
[0083] The mixed components used in Examples and Comparative Examples are as follows.
[0084] Polybutylene terephthalate resin (A)
[0085] A: Made by Toyobo Co., Ltd. Reduced viscosity 0.75 dl / g
[0086] Polyethylene terephthalate resin (B)
[0087] B: Made by Toyobo Co., Ltd. Reduced viscosity 0.63 dl / g
[0088] Thermoplastic polyester elastomer (C)
[0089] C: A thermoplastic polyester elastomer containing 75% by mass of polybutylene terephthalate and 25% by mass of polytetramethylene oxide was synthesized using dimethyl terephthalate, 1,4-butanediol and poly(tetramethylene oxide) glycol having a number average molecular weight of 1000 as raw materials.
[0090] Epoxy-containing ethylene copolymer (D)
[0091] D: "BONDFAST 7M" manufactured by Sumitomo Chemical Co., Ltd., ethylene / methyl acrylate / glycidyl methacrylate copolymer (mass ratio 64 / 30 / 6), glass transition temperature -33°C, glycidyl methacrylate content 6%
[0092] Inorganic filler (E)
[0093] E-1: Calcium carbonate: Whiten P-30 amorphous filler manufactured by Shiraishi Calcium Co., Ltd.
[0094] E-2: Glass beads: Potters-Ballotin Co., Ltd. "EGB731B" spherical filler
[0095] E-3: Mica: "GM-6" plate-shaped filler manufactured by Kinsei Matec Co., Ltd.
[0096] Glass fiber reinforced material (F)
[0097] F: Nippon Electric Glass Co., Ltd. "T-120H"
[0098] Polycarbonate resin (G)
[0099] G: Calibre 200-80, manufactured by Sumika Styron Polycarbonate Co., Ltd., melt volume flow rate (300°C, load 1.2 kg) 80 cm 3 / 10min
[0100] Ester exchange inhibitors (H)
[0101] H: Made by ADEKA, "ADEKA STAB AX-71"
[0102] Copolymerized polyethylene terephthalate resin (I)
[0103] I: Copolymer having a composition ratio of TPA / / EG / NPG=100 / / 70 / 30 mol%, manufactured by Toyobo Co., Ltd., a trial product of Toyobo VYLON (registered trademark), reduced viscosity 0.83 dl / g
[0104] Copolymer polybutylene terephthalate resin (J)
[0105] J: A copolymer having a composition ratio of TPA / IPA / / 1,4-BD=70 / 30 / / 100 mol%, manufactured by Toyobo Co., Ltd., a trial product of Toyobo VYLON (registered trademark), with a reduced viscosity of 0.73 dl / g
[0106] (The abbreviations represent TPA: terephthalic acid, EG: ethylene glycol, NPG: neopentyl glycol, IPA: isophthalic acid, 1,4-BD: 1,4-butanediol component respectively)
[0107] Examples 1 to 13, Comparative Examples 1 to 8
[0108] The polyester resin compositions of the examples and comparative examples were prepared by weighing the above raw materials according to the mixing ratios (mass %) shown in Tables 1 and 2. The twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.) was used for melt kneading at a barrel temperature of 270°C and a screw speed of 200 rpm. Raw materials other than the reinforcing material were fed into the twin-screw extruder from a hopper, and the inorganic filler (E) and the glass fiber reinforcing material (F) were fed from the exhaust port by side feed. The pellets of the obtained polyester resin composition were dried and formed into various evaluation samples by an extruder. The evaluation results are shown in Tables 1 and 2.
[0109] [Table 1]
[0110]
[0111] [Table 2]
[0112]
[0113] As can be seen from Tables 1 and 2, in Examples 1 to 13, since the mixing is carried out according to the specification of the present application, high toughness (total energy absorption in a bending test) is maintained while good sink marks are obtained, and the appearance of the molded product is also good and has a high heat deformation temperature.
[0114] On the other hand, in Comparative Example 1, the thermoplastic polyester elastomer (C) and the epoxy-containing ethylene copolymer (D) are not mixed, so the toughness is inferior to that of the examples. In Comparative Examples 2 and 3, only the thermoplastic polyester elastomer (C) or the epoxy-containing ethylene copolymer (D) is mixed, so the toughness is inferior to that of the examples. In Comparative Example 4, the content of the thermoplastic polyester elastomer (C) is small, so the toughness is inferior to that of the examples. In Comparative Example 5, the content of the spherical or amorphous inorganic filler (E) is less than the prescribed amount, so the sink mark is worse than that of the examples. In Comparative Example 6, a plate-like inorganic filler is contained instead of a spherical or amorphous inorganic filler, so the appearance of the molded product is deteriorated and the toughness is inferior to that of the examples. In Comparative Example 7, the mixing amount of the polycarbonate resin (G) is larger than the prescribed amount, so the heat deformation temperature is lower than that of the examples and the heat resistance is inferior. Comparative Example 8 contains a spherical or amorphous inorganic filler (E), and therefore has sufficient toughness even without mixing the thermoplastic polyester elastomer (C) and the epoxy-containing ethylene copolymer (D), and the sink mark is inferior to that of the Examples.
[0115] The embodiments and examples disclosed herein are to be considered in all respects as illustrative rather than restrictive examples. The scope of the present invention is indicated by the scope of the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the scope of the claims.
[0116] Industrial Availability
[0117] The thermoplastic polyester resin composition of the present invention improves the sink marks of molded products, imparts toughness, and has excellent heat resistance, so it can reduce the sink marks of products reinforced with ribs and protrusions. It is suitable for electrical products that attach importance to mechanical properties while also attaching importance to lightweight and appearance design, such as materials for housings of curling irons, dryers, etc.
[0118] Explanation of symbols
[0119] a: The short side length of the bottom is 45mm
[0120] b: The length of the long side of the bottom surface is 100mm
[0121] c: Height of the wall at the long side: 6 mm
[0122] d: Rib thickness 1mm
[0123] e: Rib length 14mm
[0124] f: Bottom thickness 2mm
[0125] g: Rib height 2mm
[0126] h: Distance from long side to rib 22mm
[0127] i: Distance from short side to rib 15mm
[0128] j: Gate width 3.8mm
[0129] k: Gate thickness 1mm
Claims
1. A polyester resin composition, characterized in that The invention comprises 18 to 35 parts by weight of a polybutylene terephthalate resin (A), 10 to 25 parts by weight of a polyethylene terephthalate resin (B), 11 to 18 parts by weight of a thermoplastic polyester elastomer (C), 1 to 4 parts by weight of an epoxy-containing ethylene copolymer (D), 12 to 20 parts by weight of an inorganic filler (E) which is not fibrous or plate-like but spherical and / or amorphous, 10 to 35 parts by weight of a glass fiber reinforcement (F), 0 to 10 parts by weight of a polycarbonate resin (G), and 0 to 2 parts by weight of an ester exchange inhibitor (H). The thermoplastic polyester elastomer (C) comprises a hard segment and a soft segment, wherein the hard segment is composed of a crystalline polyester composed of an aromatic dicarboxylic acid and an aliphatic or alicyclic diol, and the soft segment is at least one selected from the group consisting of an aliphatic polyether, an aliphatic polyester, and an aliphatic polycarbonate. The copolymerization amount of the soft segment of the thermoplastic polyester elastomer (C) is 10 to 85% by mass. The epoxy-containing ethylene copolymer (D) is an epoxy-containing ethylene copolymer comprising 50 to 99 mass % of ethylene units, 0.1 to 30 mass % of unsaturated carboxylic acid glycidyl ester units or unsaturated glycidyl ether units, and 0 to 49 mass % of ethylenically unsaturated ester compound units.
2. The polyester resin composition according to claim 1, characterized in that The present invention further contains 4 to 8 parts by mass of a copolymerized polyethylene terephthalate resin (I) and / or a copolymerized polybutylene terephthalate resin (J).
3. The polyester resin composition according to claim 1 or 2, characterized in that The polyester resin composition is injection molded at a barrel temperature of 270°C and a mold temperature of 80°C to obtain a molded product, the size of the molded product is 45mm×100mm×2mm thick, with a rib of 14mm long, 2mm high, and 1mm thick, and a 100mm side having a 6mm high wall; the sink mark depth on the back of the rib of the molded product is less than 3.0μm.
Citation Information
Patent Citations
JP1979007530B2
Polyamide resin composition and vehicle interior / exterior trim component formed of the composition
JP2009007482A
Polyamide resin composition
JP2013203869A
Resin composition for car-mounted electrical and electronic component made from flame-retardant reinforced polybutylene terephthalate and car-mounted electrical and electronic component made therefrom
JP1999335536A
Polybutylene terephthalate resin composition and its molded product
JP2001234046A